Alexander : the boy soldier who conquered the world - Adams, Simon, 1955-; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2005)
Presents an illustrated biography of Alexander the Great, the son of a Macedonian king, student of Aristotle, and conqueror of the Persian Empire.
Includes bibliographical references (p. 62) and index.
7.2
3-6
3-6
Wilson's Children
Wilson's Junior High School
Keywords: Alexander, -- the Great, -- 356-323 B.C -- Juvenile literature; Generals -- Greece -- Biography -- Juvenile literature; Greece -- Kings and rulers -- Biography -- Juvenile literature; Greece -- History -- Macedonian Expansion, 359-323 B.C. -- Juvenile literature; Alexander, -- the Great, -- 356-323 B.C.; Generals; Kings, queens, rulers, etc; Greece -- History -- Macedonian Expansion, 359-323 B.C.; Alexander, -- the Great, -- 356-323 B.C.; Generals -- Biography; Kings and rulers -- Biography; Greece -- History